Handbook on comparative and international studies in education - Sharpes, Donald K. (International perspectives on educational policy, research, and practice., 2016)
This Handbook is a comprehensive reference book for libraries, scholars, and comparative and international studies researchers. It contains 33 chapters on all major educational topics, including research using all qualitative and quantitative methodologies, with research from 23 countries and all inhabited continents. Here you as a scholar will find research from countries not usually known for published educational schooling topics. The globalization of educational research has not typically kept pace with the globalization of economies or communication technologies. This Handbook includes expanded research capabilities from both developed and less developed countries throughout the world.